The Zulu battle-axe - Maggs, T. (Southern African Humanities, 2021)
Little attention has been given previously to the occurrence of battle-axes in precolonial Natal. The accepted view has been that they were a late introduction from neighbouring areas. This paper provides a variety of evidence for greater antiquity in the region and demonstrates that the battle-axe had a cultural status of greater significance than its mere function as a hunting or fighting weapon. To cite this paper: Maggs, T. 1993. The Zulu battle-axe. Natal Museum Journal of Humanities 5: 175-88.